(untitled) - Etienne, Marie (California, 2009)
The second memoir from former Louisiana aristocrat Etienne is essentially a disjointed retread of her first, Storkbites, wrapped in the bland language of self-discovery lit and tied up with a funny new title. While covering (already-covered) topics like her abusive father, promiscuous streak, mental illness and brother's death, endless reaffirmation gives readers the feeling that Etienne still feels like a victim, and stock expressions of empowerment take the place of serious self-searching. With little in the way of conclusions or narrative arc, Etienne's tales prove frustrating and forgettable
Keywords: American fiction,Văn học Mỹ